ANALYSIS OF ORGANIZATIONAL CULTURE TO IMPROVE EMPLOYEE PERFORMANCE DISTRIBUTOR OPERATIONAL DIVISION PT. TIRTA COLOR PLAN - Tantry Irawan; Budi Rismayadi; Neni Sumarni (SEAN Institute, 2022)
The purpose of this research is the implementation of organizational culture in supporting the process of achieving the goals that have been set. In particular, this research has a target to (1) analyze how the process of implementing organizational culture in improving performance, (2) analyzing the supporting and inhibiting factors in the implementation of organizational culture in improving the performance of the operational division employees at the distributor of PT. Tirtakencana Tata Warna. This type of research is qualitative descriptive using a case study approach. Data collection techniques used by means of observation, interviews, documentation. The data obtained were validated through: a) Persistence of observation, b) Triangulation of Data Sources, c) Adequacy of Reference. The research data is processed through the following techniques: a) Data Reduction, b) Data Presentation, c) Conclusion Drawing, which aims to obtain data to support the final results of the study. The results show that the The cooperation dimension explains that a conducive work environment must be formed by leaders by creating a culture of cooperation and professionalism, so that employees will apply themselves to be professional and be able to work in teams well. The self-ability dimension describes a work environment that is not conducive because many conflicting organizational cultures can lead to a lack of work discipline, less harmonious relations between employees, teamwork does not work. The self-development dimension explains that the employee self-development program at the distributor of PT. Tirtakencana Tatawarna operational division must be supported by a strong organizational culture, so that employee performance can improve